Answer:
![a)\ x_1=-9,\ x_2=9\\\\b)\ x_1=1,\ x_2=5](https://img.qammunity.org/2023/formulas/mathematics/high-school/qfd5w5btmydohmwzcujclux3xln8th3kbj.png)
Explanation:
Given equations:
![a)\ 2x^2 - 162 = 0\\\\b) -(1)/(2)(x-3)^2=-2](https://img.qammunity.org/2023/formulas/mathematics/high-school/qdf48ma3oal8wi5j32d6j3p1ydxrwsczzl.png)
A) 2x² - 162 = 0
Step 1: Divide both sides by 2.
![\\\implies (2x^2 - 162)/(2) = (0)/(2)\\\\\implies x^2-81=0\\\\\implies x^2=81](https://img.qammunity.org/2023/formulas/mathematics/high-school/ruf2wi636l1lsq1x9g7j9om6tc5jc8ytj6.png)
Step 2: Take the square root of both sides (using both the positive and negative roots).
![\\\implies √(x^2)=√(81)\\\\\implies x=\pm\ 9](https://img.qammunity.org/2023/formulas/mathematics/high-school/26kjswoiduwxf2mw11cnm5n5qjcbckj2tb.png)
Step 3: Separate into two cases.
![\implies x_1 = -9,\ x_2 =-9](https://img.qammunity.org/2023/formulas/mathematics/high-school/dmzikialh09tazr7w59rewt8xxrrvwz4g9.png)
----------------------------------------------------------------------------------------------------------------
B) -1/2(x - 3)² = -2
Step 1: Multiply both sides by -2.
![\\\implies -2\left(-(1)/(2)(x-3)^2\right)=-2(-2)\\\\\implies (x-3)^2=4](https://img.qammunity.org/2023/formulas/mathematics/high-school/ipx36w4e877huxtd9kt8nq5brtwij9yvj6.png)
Step 2: Take the square root of both sides (using both the positive and negative roots).
![\\\implies√((x-3)^2)=√(4)\\\\\implies x-3=\pm\ 2](https://img.qammunity.org/2023/formulas/mathematics/high-school/kelhtm4jjkccyqoyfgmwk9pkau6o19li8k.png)
Step 3: Separate into two cases and solve each one.
![1)\ x-3=-2\implies x=-2+3\implies \boxed{x=1}\\\\2)\ x-3=2\implies x=2+3\implies \boxed{x=5}](https://img.qammunity.org/2023/formulas/mathematics/high-school/as0rgoxowr9o5cgwaab4vcwb1ls1nd8g4y.png)